2010
DOI: 10.1134/s1075701510050065
|View full text |Cite
|
Sign up to set email alerts
|

Predictive crystal-chemical relations in Ti-silicates based on the TS block

Abstract: In a group of minerals of reasonable complexity in which the structure topology is related but not identical, the general relation between structure topology and chemical composition is not known. This prob lem is of major significance. The structural hierarchy and stereochemistry are described for 27 titanium dis ilicate minerals that contain the TS (titanium silicate) block, a central trioctahedral (O) sheet and two adja cent (H) sheets of [5] and [6] coordinated polyhedra and (Si 2 O 7 ) groups and related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Ferraris (1997) introduced the notation HÀOÀH (by analogy with TÀOÀT) to denote two heteropolyhedral (H) sheets intercalating an octahedral (O) sheet. Sokolova (2006Sokolova ( , 2010 divided the TS-block minerals into four groups based on the different topology and stereochemistry of the TS block, and showed that these groups have different contents of (Ti + Nb). The basic unit of this series of structures is the HÀOÀH block (Fig.…”
Section: Hàoàh Structures: Ti-silicatesmentioning
confidence: 99%
“…Ferraris (1997) introduced the notation HÀOÀH (by analogy with TÀOÀT) to denote two heteropolyhedral (H) sheets intercalating an octahedral (O) sheet. Sokolova (2006Sokolova ( , 2010 divided the TS-block minerals into four groups based on the different topology and stereochemistry of the TS block, and showed that these groups have different contents of (Ti + Nb). The basic unit of this series of structures is the HÀOÀH block (Fig.…”
Section: Hàoàh Structures: Ti-silicatesmentioning
confidence: 99%
“…The TS block consists of HOH sheets (H = heteropolyhedral and O = octahedral) and is characterized by a planar cell based on translation vectors, t 1 and t 2 , with t 1 ~ 5.5 and t 2 ~ 7 Å and t 1 ^ t 2 close to 90°. The seidozerite-supergroup minerals are divided into four groups based on the content of Ti (+ Nb + Zr + Fe 3+ + Mg + Mn), topology, chemical composition and stereochemistry of the TS block (Sokolova, 2006, 2010; Sokolova and Cámara, 2013). In the rinkite, bafertisite, lamprophyllite and murmanite groups, Ti = 1, 2, 3 and 4 apfu (atoms per formula unit).…”
Section: Introductionmentioning
confidence: 99%